A review of reproduction in the seaweed genus Fucus (Ochrophyta, Fucales): Background for renewed consideration as a model organism - Hatchett, William J.; Coyer, James A.; Sjøtun, Kjersti; Jueterbock, Alexander; Hoarau, Galice (Frontiers in Marine Science, 2022)
The genus Fucus dominates the intertidal and shallow subtidal rocky reefs of the North Atlantic and also is commonly found in the intertidal of the North Pacific. It likely diversified 12.2-2.7 mya into two genetically distinct lineages: Lineage 1 with one species in the North Pacific and two in the North Atlantic; and Lineage 2 found only in the North Atlantic (one species recently introduced into the North Pacific). With 10 accepted species, Fucus spp. (and the Fucales) are unique among algae in having a diplontic life cycle, whereby the only haploid stage is the single-celled gamete. Further, Fucus spp. produce eight eggs in each oogonium; have hermaphroditic and dioecious species in each lineage; display sperm:egg ratios differing by more than one order of magnitude; have synchronized and predictable release of gametes; are capable of self- and/or cross- fertilization and asexual (fragmentation via adventitious branching) reproduction; readily hybridize in culture, as well as the field; and form ecads (free-living individuals with morphological variability linked to habitat) by hybridization or polyploidy. Consequently, the genus is an excellent model for a variety of studies in reproductive biology, employing laboratory and field manipulations as well as detailed genetic studies using the molecular ‘omics’. We review here the relevant literature in order to fully understand and appreciate the unique opportunities that Fucus spp. provide as model organisms for future studies of reproduction.